A cost-effective IoT based smart home application - (:unkn) unknown (Institute of Electrical and Electronics Engineers Inc., 2021)
The number of 9.9 billion active Internet of Things (IoT) devices in 2019 is estimated to reach 21.5 billion in 2025. In today's world, where we live in the Internet age very fast, the ever-increasing IoT applications facilitate our lives in many areas. These conveniences can also be found in today's modern home systems. The ability to real-time remote monitoring with mobile apps and remotely control home equipment are just a few of the IoT applications. In this paper, security priority real-time in-home data monitoring and control applications were carried out using ESP-WROOM-32 WiFi Bluetooth module, ThingSpeak IoT platform, Blynk iOS / Android interface developer, IFTTT and Google Assistant. The person using the house can monitor data such as temperature, humidity, illuminance, and dew point instantly through the mobile application and ThingSpeak platform through the sensors placed in various parts of the house. If the sensors do not work or encounter errors, the user will be informed via e-mail and cellphone warning message. This study's main objective is to develop secure, smart, and cost-effective IoT-based home technologies. © 2021 IEEE.
Keywords: Home automation; Internet of things (IoT); Smart home